Development of α4 integrin DNA aptamer as a potential therapeutic tool for multiple sclerosis. Issue 9 (20th May 2019) - Kouhpayeh, Shirin; Hejazi, Zahra; Boshtam, Maryam; Mirian, Mina; Rahimmanesh, Ilnaz; Darzi, Leila; Rezaei, Abbas; Shariati, Laleh; Khanahmad, Hossein
Abstract: One of the most important molecules for multiple sclerosis pathogenesis is α4 integrin, which is responsible for autoreactive leukocytes migration into the brain. The monoclonal antibody, natalizumab, was introduced to market for blocking the extravasation of autoreactive leukocytes via inhibition of α4 integrin. However, the disadvantages of antibodies provided a suitable background for other agents to be replaced with antibodies. Considering the profound advantages of aptamers over antibodies, aptamer isolation against α4 integrin was intended in the current study. The α4 integrin‐specific aptamers were selected using cell‐systematic evolution of ligands by exponential enrichment (SELEX) method with human embryonic kidney (HEK)‐293T overexpressing α4 integrin and HEK‐293T as target and control cells, respectively. Evaluation of selected aptamer was performed through flow cytometric analysis. The selected clones were then sequenced and analyzed for any possible secondary structure and affinity. The results of this study led to isolation of 13 different single‐stranded DNA clones in 11 rounds of selection which were categorized to three clusters based on common structural motifs and the equilibrium dissociation constant ( K d ) of the most stable structure was calculated. The evaluation of SELEX progress showed growth in aptamer affinity with increasing of the number of cycles. Taken together, the findings of this study demonstrated the isolation of α4‐specific single‐stranded DNA aptamers with suitable affinity for ligand, which can further be replaced with natalizumab. Abstract : We isolated and developed an α4 integrin‐specific aptamer using modified cell‐based–systematic evolution of ligands by exponential enrichment method, which could further be applied in treatment of patient with multiple sclerosis .